Mulch ado about murder - Maxwell, Edith (Maxwell, Edith. Local foods mystery., 2018)
Its been a hot, dry spring in Westbury, Massachusetts. As organic farmer Cam Flaherty waits for much-needed rain, storm clouds of mystery begin to gather ... May has been anything but merry for Cam so far. Her parents have arrived unexpectedly and her crops are in danger. But all of thats nothing compared to the grim murder of her neighbor, Nicole Kingsbury, the once proud owner of the towns new hydroponic greenhousejust after Cams mother publicly protested Nicoles use of chemicals to feed her crops. Showers may be scarce this spring, but suspects keep sprouting up. Lucky for Cam, her father turns out to have a knack for sleuthingnot to mention dealing with chickens. He and Cam will have to clear Mrs. Flahertys name quick before the killer strikes again ... Praise for the Local Foods Mysteries "Maxwells feisty heroine and the interesting background detail on the realities of organic farming blend to deliver a clever, twisting mystery." Booklist "A most enjoyable look at organic farming." Kirkus Reviews